Antimicrobial resistance of Mycobacterium avium during the COVID-19 pandemic - Vasilyeva I.A.; Panova A.E.; Tinkova V.V.; Gracheva A.N.; Kazyulina A.A.; Eliseev P.I.; Bayrakova A.L.; Samoylova A.G. (Клиническая микробиология и антимикробная химиотерапия)
Objective.